Análisis del impacto del ruido, de carácter temporal y tonal, sobre procesos cognitivos mediante auralizaciones referenciadas en un recinto pedagógico de la Universidad San Buenaventura Medellín (2017)
The project began with the investigation of D. Quintero [1], who performed the first series of psychological tests, with the intention of evaluating the affection on cognitive processes. From this idea, the pilot experiment by E. Higuita [2] was born, with some changes in the psychological tests in comparison with the D. Quintero project, the most significant was the type of noise used during the psychological tests. With a protocol to use, thanks to the pilot experiment mentioned above, this project aimed to evaluate a larger sample. Sixty-two people were evaluated, each participant performed psychological tests as Integrated Visual and Auditory Continuous Performance Test, Curve Verbal Memory, Wechsler Memory Scale and Trail Making Test, with noise conditions of 125Hz tonal noise, 500Hz, 3150Hz and intermittent noise. There is a need to evaluate the control group again, which was taken from a previous investigation; this may be due to changes to the sample and the adjustments to the protocol for this investigation. The final results shown a similar act of noise groups evaluated.